Desenvolvimento e caracterização de blendas Poli(tereftalato de etileno) - PET/ Poli(naftalato de etileno)- PEN - Nunes, Edilene de Cássia Dutra (2000)
The scientific and technological development of food packaging polymers has increased considerably over the last years, especially in relationship to packaging for beverages such as carbonated soft drinks and beer. As for carbonated soft drinks polyethylene terephthalate PET has been the most widely investigated polymer in virtue of its favorable intrinsic properties, and in recent years polyethylene naphthalate - PEN has attracted increasing interest as a result of its superior performance in relationship to PET in applications that demand higher technical requirements, however its major drawback is the high cost. One way of making PEN applications economically feasible is by blending with PET. Nonetheless, as these polymers are immiscible, conditions of process that enable an effective mixture should be looked for and, in some cases mixing of polyesters may lead to transesterification which favors miscibility between the polymers. In the current work four polymer blends were prepared from two types of PET and two types of PEN, both supplied by Eastman Chemical Company and Mitsui Co. Ltd. The premixing and processing conditions were studied, assessing the best combinations of pressure, temperature, cooling time. After specimen preparation all blends were characterized as to structural (FTIR, NMR), thermal (DSC, TGA, DMTA), mechanical (tensile test) and thermomechanical (HDT, Vicat) properties. NMR enabled confirmation and quantification of the transesterification reactions between the blend constituents responsible for blend miscibility and compatibility, notably the PET Eastman / PEN Eastman blend, which was the combination decided upon to be tested on industrial scale by injection molding of the parisons and posterior blow molding of 600 ml bottles, these were characterized in DCS, NMR and as to gas permeability.